2007
DOI: 10.1111/j.1467-9396.2007.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Passthrough Effects and Inflation Targeting in Emerging Economies: What is the Relationship?

Abstract: Several studies have shown that over the past 10 years the passthrough effect from currency depreciation into domestic inflation has been decreasing in emerging economies that adopted inflation targeting (IT) during the mid and late 1990s. Therefore the nominal exchange rate effect on domestic inflation is becoming less of an issue for these countries. The literature has offered different explanations for these declines but so far they have not been directly related to the adoption of IT. This paper shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 38 publications
3
21
0
1
Order By: Relevance
“…For all other countries the positive relationship between market inflation and export prices holds. This result is in line with what has been found in the literature (see for example Gaulier et al, 2008;Reyes, 2007;Campa and Goldberg, 2005;Taylor, 2000).…”
Section: Table 11supporting
confidence: 93%
See 1 more Smart Citation
“…For all other countries the positive relationship between market inflation and export prices holds. This result is in line with what has been found in the literature (see for example Gaulier et al, 2008;Reyes, 2007;Campa and Goldberg, 2005;Taylor, 2000).…”
Section: Table 11supporting
confidence: 93%
“…Also Taylor (2000) finds a positive relationship between ERPT and inflation. Reyes (2007) shows analytically that this positive relationship can be the direct result of implementing an 5 According to Rauch (1999), availability of information on a reference-price distinguishes homogeneous from differentiated products. Thus the differentiated products are defined as those without an organised exchange price or centralised referenceprice.…”
Section: Introductionmentioning
confidence: 94%
“…SeeReyes (2007) for a discussion on foreign exchange market interventions, IT, and the pass-through.…”
mentioning
confidence: 99%
“…One of the reasons that EMs implement an IT monetary policy after the mid-1990s currency crisis is to control for imported inflation. Reyes (2007) observed that there is a strong connection between ERPT and IT in EMs like Brazil and Mexico for the sample period under study. He provides a simple theoretical model to show that the decline in ERPT in EMs may be due to the consequence of fear of float practices.…”
Section: Literature Reviewmentioning
confidence: 86%